2021
DOI: 10.33222/juara.v6i1.1180
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Triangle Run Exercise Method in Improving Aerobic Resistance Soccer Player

Abstract: The characteristics of soccer which have a wide field and also a long duration of play require soccer players to have high aerobic endurance. Good aerobic endurance should be owned by every player in order to support a performance at the time of the field. There are so many exercises that can be used to increase endurance, but there is no reference for effective and efficient training methods for developing aerobic endurance. This study aims to test appropriate and effective training methods to increase endura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…Hasil penelitian pada efektivitas skala kecil diperoleh Pengembangan (Hardinata et al, 2021). Peningkatan tersebut terjadi karena metode latihan triangle-run memiliki kesamaan aktivitas sepakbola yaitu jalan kaki, jogging, dan sprint yang membuat pemain senang.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Hasil penelitian pada efektivitas skala kecil diperoleh Pengembangan (Hardinata et al, 2021). Peningkatan tersebut terjadi karena metode latihan triangle-run memiliki kesamaan aktivitas sepakbola yaitu jalan kaki, jogging, dan sprint yang membuat pemain senang.…”
Section: Pembahasanunclassified
“…Kelebihan metode latihan triangle in pair with soccer goals dapat meninggkatkan kualitas passing bawah dalam sepakbola, support operan pendek dalam sepakbola, dan kemampuan terobosan dalam sepakbola. Selain itu, dengan metode pelatihan segitiga berpasangan, dapat meningkatkan kerja sama tim dan metode ini memiliki kesamaan aksi dalam sepakbola yaitu jalan kaki, jogging, dan sprint yang membuat pemain senang (Hardinata et al, 2021). Hal ini karena pola interaksi antara individu memainkan peran penting dalam kinerja tim (Sumarno & Irianto, 2019).…”
unclassified
“…Kondisi fisik adalah aspek yang sangat penting dalam rangka pencapaian prestasi olahraga yang optimal (Saputro et al, 2020). Good endurance is beingable to move for a long time without feeling excessive fatigue (Hardinata at al., 2021). Kondisi fisik merupakan satu persyaratan yang dibutuhkan dalam upaya peningkatan prestasi atlet, bahkan dapat digambarkan sebagai keperluan pokok yang tidak dapat ditawartawar lagi ( Hanief et al, 2016).…”
Section: Pendahuluanunclassified
“…Although the previous research has shown the results of VO2max analysis documentation (Supriatna et al, 2023;Yanti et al, 2022) and specifically presented the VO2max of football athletes (Allsabah, 2021;Nirwandi, 2017;Sinurat, 2019), it further discusses the differences in VO2max between athletes and nonathletes (Kostić, 2017), as well as field tests to predict VO2max in hockey players (Morton & Klein, 2019). However, this study offers an offer from a different perspective from previous research, namely the instrument used to measure the athlete's VO2max using the Yo-Yo Intermittent Recovery Test level 2 (YIRT2) where the Yo-Yo test is a valid test used to measure VO2max in football athletes (Hardinata et al, 2021). In addition, the level 2 Yo-Yo test has been indicated as an anaerobic-based field test (Castagna et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Besides, football is also a game that requires a lot of energy to boost enthusiasm in a team (Syukur & Soniawan, 2015). Therefore, football players are required to have good physical and aerobic conditions so that the game can run well (Hardinata et al, 2021). Thus, the ability of VO2max becomes the greatest aerobic exercise (Gumantan & Fahrizqi, 2020) where this ability is also often said to be the soul of its appearance to improve good physical work (Debbian & Rismayanthi, 2016).…”
Section: Introductionmentioning
confidence: 99%